2009
DOI: 10.1158/1535-7163.mct-09-0448
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic cannabinoid receptor agonists inhibit tumor growth and metastasis of breast cancer

Abstract: Cannabinoids have been reported to possess antitumorogenic activity. Not much is known, however, about the effects and mechanism of action of synthetic nonpsychotic cannabinoids on breast cancer growth and metastasis. We have shown that the cannabinoid receptors CB1 and CB2 are overexpressed in primary human breast tumors compared with normal breast tissue. We have also observed that the breast cancer cell lines MDA-MB231, MDA-MB231-luc, and MDA-MB468 express CB1 and CB2 receptors. Furthermore, we have shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
229
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(240 citation statements)
references
References 48 publications
4
229
1
2
Order By: Relevance
“…Recently, numerous studies have evidenced the role of cannabinoids as potential anti-tumoral drugs owing to their ability to reduce tumor in different animal models, including glioma, 6 breast cancer 7,8 and prostate cancer. 9,10 Recent research has also reported that the synthetic cannabinoid WIN-55 212-2 inhibits HCC growth.…”
mentioning
confidence: 99%
“…Recently, numerous studies have evidenced the role of cannabinoids as potential anti-tumoral drugs owing to their ability to reduce tumor in different animal models, including glioma, 6 breast cancer 7,8 and prostate cancer. 9,10 Recent research has also reported that the synthetic cannabinoid WIN-55 212-2 inhibits HCC growth.…”
mentioning
confidence: 99%
“…Notably, it is well-known that long-term use of estrogens can promote carcinogenesis, particularly in breast and endometrial cancer (32)(33)(34). Secondly, a number of studies indicate that the endocannabinoid system plays protective roles against the growth and the spreading of several types of carcinomas, including endometrial and breast cancers (35,36). Therefore, a combination of cannabinoids and estrogens may have beneficial effects by inhibiting estrogen-induced carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The results of preclinical trials suggest that these agents may prove to be of use for patients experiencing nausea and vomiting due to radiation therapy (Darmani et al, 2007). Cannabinoids are also known to suppress growth or promote cell death in a variety of cancer cell lines, including glioma, pancreatic, melanoma, lymphoma, lung, and breast (Carracedo et al, 2006;Qamri et al, 2009;Salazar et al, 2009;McAllister et al, 2011;Preet et al, 2011;Scuderi et al, 2011;Wasik et al, 2011). Given that cannabinoid-based drugs are used for suppression of nausea and for appetite stimulation in patients with cancer, as well as their potential utility as adjunctive treatments along with conventional therapies such as radiation, the present studies were initiated to determine whether cannabinoids might augment the antiproliferative actions of radiation in breast tumor cells.…”
Section: Introductionmentioning
confidence: 99%